THE GREEN POLITICAL PERSPECTIVE IN COASTAL AREA MANAGEMENT POLICY IN JENU SUB DISTRICT, TUBAN REGENCY - Sri Musrifah (Universitas Muhammadiyah Sidoarjo, 2020)
This study aims to describe the green political view of coastal area management in Jenu sub-district, Tuban Regency. The location is in Jenu sub-district, Tuban district, with a research focus on the coastal area of the Jenu sub-district, Tuban district. By using a green political perspective, qualitative methods and in-depth interviews, direct observa- tion and documentation in the data. The research informants were the administrators of the Tuban Mangrove Center, the District Government of Jenu, Tuban Regency, the Envi- ronmental Service of Tuban Regency, the Department of Fisheries and Animal Husbandry of Tuban Regency, and the people living in the coastal area of Jenu sub-district. The results showed that from a green political perspective, the management of coastal areas in Jenu sub-district, Tuban district, has not met the goals and targets that are expected to increase economic growth without destroying the natural and social ecosystems of the coastal area. Efforts to exploit coastal areas by illegal mining of sea sand and reclamation to build several infrastructures have resulted in natural damage in the form of shoreline retreat, accretion and abrasion. The Tuban regency government, with the AMDAL permit that has been issued, is part of the cause of the damage to the coastal area of the Jenu Tuban sub-district today.